A PROPÓSITO DE LA ACTUALIDAD DE LA DISCUSIÓN SOBRE LOS CONSEJOS Y LOS CONCEPTOS DE CONSEJOS - Meschkat, Klaus (La Sociología en sus Escenarios, 2012)
Abstract.Professor Klaus Meschkat analyzes the intention to complement or to replace the State, defined in the Constitution of Venezuela of 1999, in democratic form by the route of the "Communal Council", project impelled by the government of president Chávez of Venezuela. Meschkat poses some questions that arise necessarily when somebody dares to proclaim a socialism of century 21. No of the present of Latin America leftist regimes was born by the revolutionary route. They are the result of gained more or less spectacular electoral victories with the rules of a bourgeois-representative democracy. The old state apparatus, stayed and, mainly, the already existing Armed Forces were conserved like separated part of the state apparatus. Generally, the new agent chief executives economically made sure loyalty the military - armoring legal and economically the institution with the maintenance of their privileges (own budgets, amnesties, and autonomy). Resumen.El Profesor Klaus Meschkat analiza el propósito de complementar o reemplazar el Estado, definido en la Constitución de Venezuela de 1999, en forma democrática por la vía de los "consejos comunales", proyecto impulsado por el gobierno del presidente Chávez de Venezuela. Meschkat plantea algunas preguntas que surgen necesariamente cuando alguien se atreve proclamar un socialismo del siglo 21. Ninguno de los actuales regímenes de izquierda de América Latina nació por la vía revolucionaria. Son el resultado de victorias electorales más o menos espectaculares logradas con las reglas de una democracia burgués-representativa. El viejo aparato estatal, se mantuvo y, sobre todo, las Fuerzas Armadas ya existentes se conservaron como parte separada del aparato estatal. Por lo general, los nuevos mandatarios se aseguraron la lealtad de los militares - blindando legal y